2016
DOI: 10.5539/ass.v12n4p171
|View full text |Cite
|
Sign up to set email alerts
|

The Help-seeking from Social Capitals and Self-regulated Learning among Pre-service Teachers

Abstract: This study aims to investigate the help-seeking subjects for pre-service teachers in need of suggestions for practicum and to determine the prediction of pre-service teachers' social capitals for help-seeking on their self-efficacy for help-seeking and self-regulated learning. A total of 223 pre-service teachers, from a teacher education university at the middle of Taiwan, were invited to fill in the validated questionnaire in October 2015.The analytical results of this study by Chi-square Test achieve signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…They did help-seeking to get external assistance to deal with the issues, such as asking their peers, friends, home-room teacher, and tutor (P1, P4, and P5). These results were akin to the study from Liu (2016) relating to the willingness to help-seeking from the teachers and peers that had the same teaching practicum in the school.…”
Section: Reflecting and Adaptive Help-seekingmentioning
confidence: 56%
See 1 more Smart Citation
“…They did help-seeking to get external assistance to deal with the issues, such as asking their peers, friends, home-room teacher, and tutor (P1, P4, and P5). These results were akin to the study from Liu (2016) relating to the willingness to help-seeking from the teachers and peers that had the same teaching practicum in the school.…”
Section: Reflecting and Adaptive Help-seekingmentioning
confidence: 56%
“…From their experiences in overcoming the problems they faced in a teaching practicum in school, the pre-service teachers did reflection and help-seeking. Furthermore, pre-service teachers tended to ask their friends and peers about the solution and share their problems (P8 and P20), as also mentioned by Liu (2016) in his study about help-seeking among preservice teachers. Pre-service teachers did reflection and its results were used to solve their problems (Mumford & Dikilitaş, 2020).…”
Section: Reflecting and Adaptive Help-seekingmentioning
confidence: 85%
“…Teacher training studies (Dermitzaki & Kriekouki, 2017 ; Liu, 2016 ), found that experience sharing could be a potential SRL training method for students. Powers ( 2006 ) states that low-achieving design students are less likely to utilize goals to connect with peers, as a result of which they interact less with their peers as they deliberate on their studio performance.…”
Section: Discussionmentioning
confidence: 99%